An analysis of lateralized neural crest marker expression across development in the Mexican tetra, Astyanax mexicanus - Gross, Joshua B.; Berning, Daniel; Phelps, Ayana; Luc, Heidi (Frontiers in Cell and Developmental Biology, 2023)
The biological basis of lateralized cranial aberrations can be rooted in early asymmetric patterning of developmental tissues. However, precisely how development impacts natural cranial asymmetries remains incompletely understood. Here, we examined embryonic patterning of the cranial neural crest at two phases of embryonic development in a natural animal system with two morphotypes: cave-dwelling and surface-dwelling fish. Surface fish are highly symmetric with respect to cranial form at adulthood, however adult cavefish harbor diverse cranial asymmetries. To examine if lateralized aberrations of the developing neural crest underpin these asymmetries, we used an automated technique to quantify the area and expression level of cranial neural crest markers on the left and right sides of the embryonic head. We examined the expression of marker genes encoding both structural proteins and transcription factors at two key stages of development: 36 hpf (∼mid-migration of the neural crest) and 72 hpf (∼early differentiation of neural crest derivatives). Interestingly, our results revealed asymmetric biases at both phases of development in both morphotypes, however consistent lateral biases were less common in surface fish as development progressed. Additionally, this work provides the information on neural crest development, based on whole-mount expression patterns of 19 genes, between stage-matched cave and surface morphs. Further, this study revealed ‘asymmetric’ noise as a likely normative component of early neural crest development in natural Astyanax fish. Mature cranial asymmetries in cave morphs may arise from persistence of asymmetric processes during development, or as a function of asymmetric processes occurring later in the life history.